License to Compete : Reforming the Regulation of Professions in Croatia - World Bank Group (World Bank, Washington, DC, 2020)
Removing regulatory barriers in services is key to unlocking productivity in Croatia. Croatia has more restrictive regulations than most other EU member states, and prior World Bank research shows that the economic gains to reforms are the highest out of all EU countries. This report provides recommendations on specific measures to reform the regulation of professions. The report focuses on reforms for 24 high-impact occupations which were selected for review based on their economic relevance, the restrictiveness of regulations, and the feasibility of reforms. The World Bank identified 42 restrictions that are most harmful to competition based on market effects. The World Bank recommends the adoption of an omnibus bill covering 45 measures across 24 professions. The recommended measures require changes in 19 laws and 52 by-laws under the responsibility of seven ministries and constitute reforms with high potential to bring productivity gains. The recommended reforms are a cornerstone of the National Reform Program of the Republic of Croatia, the Structural Reform Support Program of the European Commission, and the World Bank Group’s Country Partnership Framework.